Increasing the Efficiency of the Cadmium Telluride Solar Cell by Increasing the Number of Absorber Layers and Optimizing Its Efficiency - Aylin Saeedi; Mohammad Karimi; Hakimeh Mohammadpour (Advances in Condensed Matter Physics)
To reduce the recombination of carriers, the number of layers were increased from 5-layer to 9-layer solar cells while keeping other effective parameters intact. In this work, the efficiency of the cell is increased from 25.93% to 28%, which means a relative increase of 8.2%. The change in impurity density and the length of the layers are employed to achieve maximum efficiency. Increasing the number of layers of the proposed structure does not necessarily lead to an efficiency increment. In this paper, we design a new multijunction solar cell with 9-layer structure that has higher efficiency as compared to the 5-layer counterpart. The performance of cadmium sulfide-cadmium telluride (CdS/CdTe) multijunction solar cells is numerically investigated. Because of the flexibility of the proposed model and feasible construction of the structure, the cell characteristics obtained by this program can be examined by experiment. This structure, accompanied by multilayers of n-CdTe and p-CdTe (n-SnO2/n-CdS/p-CdTe/n-CdTe/p-CdTe/n-CdTe/p-CdTe/p+-Cu2O) are investigated with different thicknesses, doping densities and number of layers.